Considerations for a Research Program on Drought in Mexico - Magaña, Víctor (Tecnología y ciencias del agua, 2016)
The impacts of drought in Mexico have led water authorities to define a strategy for action to diminish their costs. But the proposed actions at regional levels require a solid scientific basis on the subject to answer several of the questions that decision makers have, not only on the dynamics of climate variability, but on the context that produces hydrological, agricultural and socioeconomic droughts. This work makes some considerations on the research topics and approach to be followed in the scientific Plan for the Program against Drought in Mexico (known as Pronacose), in a risk management context. This approach requires that, in addition to monitoring strategies and the study of processes and prediction on drought, vulnerability be characterized as a dynamic and multifactorial element within the analysis on risk to drought. This approach also requires the collaboration of stakeholders from various sectors and regions, in order to define structural and non-structural measures against drought, such as early warning systems.